Effect of wet treatment with NaOH on the disappearance of dry matter and carbohydrates from barley straw incubated in sacco (Semiárida, 2020)
The effect of wet NaOH treatment on dry matter and carbohydrates disappearance of barley straw from nylon bags incubated in saco. Treated (CT) and untreated (CS) barley straw sample were incubated in the rumen of one cow for 2, 6, 12, 24, 48 and 72 hours. Disappearance of dry matter, organic matter, individual sugars, cellulose and hemicellulose was measured. The cow was fed a barley straw (untreated) diet supplemented with fishmeal, rolled barley and a mineral-vitamine mixture. The chemical treatment of the straw was a modification of the Beckmann method; the chemical reactant was sodium hydroxide and the process consisted in a solubilization in diluted NaOH solution. The method used was systematized in. way that the water used for washing out the solubilized matter was reused for the solubilization itself. The treatment was highly effective in improving the degradation of straw in the rumen. AII the degradation curves showed higher value for untreated straw than for treated straw al 2 h of incubation; these differences were presumably due lo loses of water soluble substances and fine particles from the untreated straw and not lo true digestion. From 6 h onwards the treatment with alkali produced a higher digestion in dry matter, organic matter and all sugar and polysaccharides, except cellulose, which digestion was only higher intreated straw from 24 h onwards. Degradability were: dry matter: CT: 62.7; CS: 40.7; organic matter: CT: 60.8; CS: 39.9; arabinose: CT: 68.1; CS: 52.9; mannose: CT: 63.4; CS: 44.6; galactose: CT: 69.8; CS: 54.4; xylose: CT: 70.1; CS: 46.6; hemycellulose: CT: 69.8; CS:47.1; cellulose: CT: 660.8: CS: 45.3. All differences between treatment were significant at 1% level.
Keywords: barley straw; wet NaOH treatment; nylon bag; digestion; carbohydrates